Altered Integrative and Conjugative Elements (ICEs) in Recent Vibrio cholerae O1 Isolated From Cholera Cases, Kolkata, India - Sarkar, Anirban; Morita, Daichi; Ghosh, Amit; Chowdhury, Goutam; Mukhopadhyay, Asish K.; Okamoto, Keinosuke; Ramamurthy, Thandavarayan (Frontiers in Microbiology, 2019)
The self-transferring integrative and conjugative elements (ICEs) are large genomic segments carrying several bacterial adaptive functions including antimicrobial resistance (AMR). SXT/R391 family is one of the ICEs extensively studied in cholera-causing pathogen Vibrio cholerae. The genetic characteristics of ICE-SXT/R391 in V. cholerae are dynamic and region-specific. These ICEs in V. cholerae are strongly correlated with resistance to several antibiotics such as tetracycline, streptomycin and trimethoprim-sulfamethoxazole. We screened V. cholerae O1 strains isolated from cholera patients in Kolkata, India during 2008-2015 for antibiotic susceptibility and the presence of ICEs and subsequently sequenced their conserved genes. Resistance to tetracycline, streptomycin and trimethoprim-sulfamethoxazole was detected in strains isolated during 2008-2010 and 2014-2015. The genes encoding resistance to tetracycline (tetA), trimethoprim-sulfamethoxazole (dfrA1 and sul2), streptomycin (strAB) and chloramphenicol (floR) were detected in the ICEs of these strains. There was a decrease in overall drug resistance in V. cholerae associated with the ICEs in 2011. DNA sequence analysis also showed that AMR in these strains was conferred mainly by two types of ICEs, i.e., ICETET (comprising tetA, strAB, sul2 and dfrA1) and ICEGEN (floR, strAB, sul2 and dfrA1). Based on the genetic structure, Kolkata strains of V. cholerae O1 had distinct genetic traits different from the ICEs reported in other cholera endemic regions. Transfer of AMR was confirmed by conjugation with sodium azide resistant Escherichia coli J53. In addition to the acquired resistance to streptomycin and trimethoprim-sulfamethoxazole, the conjugally transferred (CT) E. coli J53 with ICE showed higher resistance to chloramphenicol and tetracycline than the donor V. cholerae. Pulsed-field gel electrophoresis (PFGE) based clonal analysis revealed that the V. cholerae strains could be grouped based on their ICEs and AMR patterns. Our findings demonstrate the epidemiological importance of ICEs and their role in the emergence of multidrug resistance (MDR) in El Tor vibrios.